MEMAKNAI MODERASI BERAGAMA DALAM BUNDARAN 1001 AI SINGKAWANG - Moriansyah, Mori; Erwin; Hamzah, Nur; maftuhah, Maftuhah (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study analyzes the historical, symbolic, and religious moderation values ​​contained in the AI ​​1001 Roundabout in Singkawang. This monument not only functions as an aesthetic element of the city, but also represents social harmony and inter-ethnic tolerance. The existence of statues of the three main ethnic groups, Malay, Chinese, and Dayak, emphasizes the collective identity of the Singkawang community who live in diversity and peace. This study uses a qualitative approach with a hermeneutic method to interpret the symbolic meaning contained in the monument. The results of the study indicate that the AI ​​1001 Roundabout plays a role in strengthening the values ​​of religious moderation, which include tolerance, anti-violence, adaptation to local culture, and love for the homeland. In addition, the existence of this monument also contributes to building collective awareness of the community regarding the importance of pluralism and unity amidst differences. Singkawang's predicate as the Most Tolerant City in Indonesia further strengthens the role of the AI ​​1001 Roundabout as a real symbol of harmony. Thus, this monument is not only an icon of the city, but also a means of education and social integration in creating a harmonious and inclusive environment for the entire community.